PP41 Simulated ambulance shifts using virtual reality: a service evaluation. Issue 9 (23rd August 2022) - Johnston, Sasha; Strong, Gary; Knowles, Steve
Abstract : Background: One of the consequences of delivering the frontline response during the COVID-19 pandemic has been the reduced capacity of UK Ambulance organisations to provide practical placement opportunities for undergraduate paramedic students. In lieu of traditional ambulance shifts, Virtual Reality (VR) can be used to simulate experiences without the student going through the real event. This service evaluation explores student feedback to understand whether VR technology could bridge the gap. Methods: Framed by the Plan, Do, Study, Act [PDSA] improvement cycle a series of VR simulated scenarios, related to mapped learning outcomes, supplemented practical ambulance placements for undergraduate paramedic students in south west England during the COVID-19 pandemic. Following simulated sessions, participating students were asked to voluntarily complete feedback questionnaires. Using Likert-scale questions, students were asked to rate the quality of tutors and the session content. Collated comments were entered into an Excel spreadsheet and content analysis was used to code and categorise responses based upon frequency. Results: Results are based on eighty-eight nodes systematically generated from free-text feedback comments provided by fifty-three students who undertook a simulated practice placement utilising VR during April and May 2021. Nodes were reduced to fourteen categories and then condensed into nine themes relating to three domains of learning; affective, psychomotor and cognitive. An overarching theme of 'enthusiasm for VR learning' was identified. Conclusions: Overall, the utilisation of VR during simulated scenarios for undergraduate paramedic students appears to be a useful and acceptable adjunct to traditional ambulance shifts. The VR approach appears to be particularly useful for supporting the affective domain of learning with several students reporting increased self-confidence, positive interactions with course facilitators and the opportunity to put classroom knowledge into practice. We recommend that future use of VR should pay particular attention to the quality of simulations and the equipment used.